Transformation of innovative digital technologies - A. Obukhova; E. Ershova; A. Sotnikov (Вестник Северо-Кавказского федерального университета, 2022)
The article explores the modern challenges facing the system of higher education, global transformation processes and the impact of innovative digital transformative technologies technologies influencing all spheres of development of modern society.   The purpose of the article is to find out to develop the relationship between employment problems and professional digital competencies that are in demand students of economic specialties; propose implementation management measures competence models of advanced development. It is concluded that the efficiency of economics in these conditions is directly dependent on the degree of digitalization of society.   The main factors of this process are human and intellectual capital, which, in terms of competencies, must meet the needs of the world being updated.